2014
DOI: 10.5539/ep.v3n3p56
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides in Sediment-Dwelling Animals from Mangrove Areas of the Calabar River, SE Nigeria

Abstract: Sediment-dwelling biota such as mollusks (clam) and crabs collected from mangrove areas of the Calabar River are important routes of exposure to organochlorine pesticides (OCPs) contamination. Residual levels of OCPs including HCHs, DDTs, heptachlor, heptachlor epoxide, aldrin, endrin ketone, entrin aldehyde, dieldrin, endosulfan, endosulfan sulphate, methoxychlor, were determined in these organisms. The results revealed the OCP loads to be predominated by DDTs and HCHs (much of which was derived from illegal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…γ-HCH, the major component of lindane was detected at a mean level of 0.044 mg kg -1. The HCH isomers (α, β, γ-HCH) detected have also been reported in animal products [34,46]. The higher concentration of α-HCH isomer recorded in this study compared to other isomers may be attributed to the relatively high volatility of this isomer whose uptake increases via deposition from the atmosphere or by direct treatment with pesticides [47].…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…γ-HCH, the major component of lindane was detected at a mean level of 0.044 mg kg -1. The HCH isomers (α, β, γ-HCH) detected have also been reported in animal products [34,46]. The higher concentration of α-HCH isomer recorded in this study compared to other isomers may be attributed to the relatively high volatility of this isomer whose uptake increases via deposition from the atmosphere or by direct treatment with pesticides [47].…”
Section: Resultssupporting
confidence: 60%
“…. The cyclodienes group which include dieldrin, aldrin, endrin and endosulfan have been reported in some food products in Nigeria [30,31,34]. The mean concentration of aldrin was 0.156 mg kg -1 , while the mean concentration of endosulfan metabolite gave 0.076 mg kg -1 αendosulfan, 0.243 mg kg -1 β-endosulfan and 0.218 mg kg -1 endosulfan sulphate with total endosulfan concentration of 0.537 mg kg -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage total organic carbon (TOC), available sulfur (S), iron (Fe) and pH contents of sediments in each microcosm were analyzed following standard methods [15] before the start (initial) and after 30 days (final) of the experiment. Following the initial decarbonation protocol, TOC was determined as previously reported by Oyo-Ita et al [16] using flash combustion at 1024 o C and thermal conductivity detection in triplicate with a CHNS Elemental Analyser (Carlo Erba 1108).…”
Section: Sediment and Water Analysismentioning
confidence: 99%
“…Many studies showed that young animals usually lack resistance against pollutants because of their underdeveloped organs and weaker immunity [11]. In some pollution studies, for instance, it was also observed that small mollusks and crabs accumulated more α-HCH [16] and PAHs in shrimps [32] than their larger counterparts. This observation was supported by the fact that smaller individuals have faster rates of uptake but slower rates of elimination of hydrophobic contaminants than their larger counterparts [33].…”
Section: Polychaetes Survival Variations In Dissolve Oxygen With Temperature and Ph Of Watermentioning
confidence: 99%